Quantitative Cerebrovascular Reactivity in Normal Aging: Comparison Between Phase-Contrast and Arterial Spin Labeling MRI - Taneja, Kamil; Liu, Peiying; Xu, Cuimei; Turner, Monroe; Zhao, Yuguang; Abdelkarim, Dema; Thomas, Binu P.; Rypma, Bart; Lu, Hanzhang (Frontiers in Neurology, 2020)
Purpose: Cerebrovascular reactivity (CVR) is an index of the dilatory function of cerebral blood vessels and has shown great promise in the diagnosis of risk factors in cerebrovascular disease. Aging is one such risk factor; thus, it is important to characterize age-related differences in CVR. CVR can be measured by BOLD MRI but few studies have measured quantitative cerebral blood flow (CBF)-based CVR in the context of aging. This study aims to determine the age effect on CVR using two quantitative CBF techniques, phase-contrast (PC) and arterial spin labeling (ASL) MRI. Methods: In 49 participants (32 younger and 17 older), CVR was measured with PC, ASL, and BOLD MRI. These CVR methods were compared across young and older groups to determine their dependence on age. PC and ASL CVR were also studied for inter-correlation and mean differences. Gray and white matter CVR values were also studied. Results: PC CVR was higher in younger participants than older participants (by 17%, p = 0.046). However, there were no age differences in ASL or BOLD CVR. ASL CVR was significantly correlated with PC CVR (p = 0.042) and BOLD CVR (p = 0.016), but its values were underestimated compared to PC CVR (p = 0.045). ASL CVR map revealed no difference between gray matter and white matter tissue types, whereas gray matter was significantly higher than white matter in the BOLD CVR map. Conclusion: This study compared two quantitative CVR techniques in the context of brain aging and revealed that PC CVR is a more sensitive method for detection of age differences, despite the absence of spatial information. The ASL method showed a significant correlation with PC and BOLD, but it tends to underestimate CVR due to confounding factors associated with this technique. Importantly, our data suggest that there is not a difference in CBF-based CVR between the gray and white matter, in contrast to previous observation using BOLD MRI.